Constitutional control of the Caretaker Government - Shendi Habib, Researcher. Alia; Majid Jassem, Assist . Prof . Batoul; Atwan Khalaf , Prof. Dr. Muhammad (Basra studies journal, 2023)
This research sheds light on the supervisory role exercised by constitutional judiciary over the activities and conduct of the caretaker government. It explores the conditions and the locus standi of constitutional lawsuits and the impact of formal and substantive violations committed by this government. The study also investigates how the constitutional judiciary, represented by the Supreme Federal Court, addresses these issues. It delves into the legal obstacles hindering the court’s ability to fulfill its role in a manner that upholds the principle of legitimacy and the rule of law by ensuring the caretaker government adheres to the correct path. The comparative method was adopted, comparing with France and Lebanon, to study how constitutional oversight is exercised in these two countries and whether it includes scrutiny of systems or government decisions or is limited to laws only. The findings reveal that both France and Lebanon restrict the oversight of constitutional judiciary to laws and decisions with the force of law. Administrative justice exercises oversight over other decisions. In Iraq, the constitutional judiciary oversees both laws and systems without discrimination, as long as they are enforceable. Administrative justice also oversees governmental decisions, especially those of a purely administrative nature. The research concludes that the Supreme Federal Court in Iraq needs legislation precisely defining the types of government decisions subject to its oversight. Additionally, legislation is needed regarding one of its important powers: deciding on accusations against the government.